Temporal diagenetic alternations in Adélie penguin eggshells throughout the late holocene of Antarctica - Cavallerano, Edward J.; NC DOCKS at The University of North Carolina Wilmington (2009)
Data from scanning electron microscopy (SEM) coupled with energy dispersive X-ray (EDX) analysis of late Holocene Adélie penguin (Pygoscelis adeliae) eggshell fragments were used to investigate the role of diagenesis on paleoecological reconstructions using stable isotopes. The results of this study demonstrate that clear diagenetic alterations occur in eggshell carbonate following burial in ornithogenic, or bird formed, soils. Diagenesis progresses from blocky calcium carbonate (CaCO3) rhombs in the modern eggshells to botryoidal fluorapatite crystals (Ca5(PO4)3F), as indicated by the increased weight percentages of phosphorus and fluorine with sampling depth. Carbon weight percent was found to decrease, with statistical significance, in relation to phosphorus, indicating that carbon is preferentially removed from the eggshell through time. Diagenesis in the fossils is predictable, with early stage alterations occurring along the outer margins of the eggshells first, and slowly progressing inward towards the center. Despite these trends, the inclusion of unaltered CO3 2- from the original eggshell material allows for the fossil’s use in isotopic reconstructions.